Estrategia de servicio y fidelización de clientes en la empresa Agropecuario Campo Verde S.A., Coronel Portillo 2023 - Zaldivar Rivero, Misael (2023)
The present final report was to determine the relationship between the service strategy and customer loyalty in the company Agropecuario Campo Verde S.A., Coronel Portillo 2023, opting for an applied study with a non-experimental design; made up of a population of 92 clients, to whom the questionnaire was applied to collect accurate information. Therefore, it was concluded that the company's service strategy has been qualified as regular by 38%, this is because it sometimes provides detailed information about the product and the purchase process, as well as information about the products in networks. social. However, personalized attention is generally offered with a secure infrastructure, equipment that works correctly, and good customer service so that they feel confident. For its part, customer loyalty is rated as medium (41%) because it offers a quality product, but it presents problems in terms of quantities, size, weight and characteristics, this has affected customer loyalty, the The main problem is the service offered by the staff, who tend to be unfriendly and empathetic, which prevents them from achieving a higher level of loyalty. Concluding that, there is a significant relationship between the variables, being demonstrated by a Pearson coefficient and significance (r=0.994; p=0.000) which is within the very strong positive level.